2020
DOI: 10.1177/0733464820967195
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Virtual Arts Recreation for Wellbeing Promotion in Long-Term Care Residents

Abstract: The efficacy of a technology-driven visual arts recreation activity, delivered virtually, was evaluated for its potential to achieve positive impacts, similar to traditional arts-interventions, on wellbeing in long-term care residents. Thirty-one residents (average age 86.8 years; SD = 9.4) engaged with the arts-intervention for 30-minutes, twice weekly, for 6 weeks with either a partner or as part of a group. Wellbeing indicators included self-reported psychological and health-related wellness, and attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Using an integrated knowledge translation perspective, 50 the team members continue the development of this virtual recreation app that has already shown promise in improving self-reported wellness when used with older adults in long-term care. 37 The next steps include sensory accessibility adjustments (improved access to contrast and magnification features and audio files) as well as the refinement of a more user-friendly tactile interface for tablet computer users. Thereafter, its evaluation will focus on exploring its potential health benefits over time in older adults living with LV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an integrated knowledge translation perspective, 50 the team members continue the development of this virtual recreation app that has already shown promise in improving self-reported wellness when used with older adults in long-term care. 37 The next steps include sensory accessibility adjustments (improved access to contrast and magnification features and audio files) as well as the refinement of a more user-friendly tactile interface for tablet computer users. Thereafter, its evaluation will focus on exploring its potential health benefits over time in older adults living with LV.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research with AotB has relied on testing the application with normally sighted older adults, and preliminary data show that participants are able to independently navigate the application and report enjoying the AotB application. 37 The application has also been tested as a group intervention with older adults with mild to moderate dementia who are residing in long-term care and results show improved wellbeing in participants following access to the activity. 37 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, research has found that digital art viewing is able to influence people's emotions, including reducing negative emotion (Cotter et al, in press;Trupp et al, 2022Trupp et al, , 2023 and increasing positive emotion (Cotter et al, in press; Igdalova & Chamberlain, in press). Further, digital art engagement has been particularly of interest within populations that may have difficulty physically going to an art museum (e.g., individuals with dementia, Tyack et al, 2017;older adults, Averbach & Monin, 2022, Murphy et al, 2021, with promising initial results.…”
Section: The Well-being Benefits Of Virtual Art Galleries: Examining ...mentioning
confidence: 99%
“…New programs and programs that were once delivered in person, were now being offered through asynchronous and synchronous settings. Recent research in virtually delivered programs demonstrates that technology may be an effective platform for increasing accessibility for audiences to these experiences ( 24 ), with one intergenerational, music-based virtual study noting “the use of simple and free computer technology (e.g., Dropbox, tablets, smartphones) could be a promising vehicle for communicating, learning, and enhancing relationships between opposite generations” ( 11 ). One example of adapting in person sessions to telehealth was conducted by McAulay, Block, Booth, and Cowley ( 25 ).…”
Section: Introductionmentioning
confidence: 99%